Analysis the Relationship Between Government’s Revenue, Expenditure and Gross Domestic Product: Evidence of Lao PDR - PHANTHASITH, Somsanith; CHANTHAVONE , Thongphan; HER, Pheng (Journal of Management Science Nakhon Pathom Rajabhat University, 2023)
The government's income-expenditure performance indicates the government's financial position and is an important indicator for macroeconomic development planning. Therefore, the researcher aims to test the relationship between Lao government's revenue, expenditure and gross domestic product (GDP) by using the Cointegration and Error Correction model with the time series data from 1990-2019. The results of the study found that there is a relationship in both the short-run and long-run. In the long-run, both revenue and GDP have a positive significant relationship on expenditure with a significance level of 0.01 and 0.1 respectively. For short-run, only government’s revenue has a statistically significant relationship with government spending at a significance level of 0.01, with the coefficient of ECT equal to -0.781. In the test of residual normality distributed and serial correlation indicates we cannot reject null hypothesis, meaning that the model used in this study is suitable for testing the relationship between revenue, expenditure and GDP of Lao PDR.The researchers also suggest that the government should decide on expenditure and revenue side by side by increasing revenue and reducing expenditure simultaneously to manage the budget deficit because the increase in public spending helps to stimulate economic activities which will result in an increase in government revenue. However, this study uses a small sampling and is a study of only one country. Therefore, further researchers should consider panel data and use more independent variables in order to more accurate predict. Article history: Received 13 January2023 Revised 7 May 2023 Accepted 8 May 2023 SIMILARITY INDEX = 0.00 %